1992
DOI: 10.3322/canjclin.42.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Dermatofibrosarcoma protuberans

Abstract: Dermatofibrosarcoma protuberans is an intermediate-grade sarcoma that arises in the dermis of the trunk, proximal extremities, and less commonly, in the head and neck area of adults. Dermatofibrosarcoma protuberans has a deceptively innocuous early clinical appearance and generally exhibits an indolent course for years before entering a rapid growth phase. Its locally invasive behavior results in early recurrence if prompt, wide excision is not performed. Dermatofibrosarcoma protuberans rarely metastasizes thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 32 publications
1
76
0
1
Order By: Relevance
“…1,2 It is believed that metastases develop more commonly in DFSP harboring areas of fibrosarcoma, known as fibrosarcomatous DFSP (DFSP-FS). [3][4][5][6] If metastases occur, they often are localized in the lungs and are less commonly localized in lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is believed that metastases develop more commonly in DFSP harboring areas of fibrosarcoma, known as fibrosarcomatous DFSP (DFSP-FS). [3][4][5][6] If metastases occur, they often are localized in the lungs and are less commonly localized in lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…The dorsal skinfold chamber is a widely used in vivo model for preclinical cancer research for drug testing, angiogenesis and tumor progression studies, as well as vascular leakage and intratumoral pressure measurements (Asaishi et al 1981;Boucher et al 1996;Guba et al 2002;Leunig et al 1992;ReyesAldasoro et al 2008). A suitable tumor type for the monitoring of active invasion in this window model are HT-1080 Wbrosarcoma cells, that clinically originate from connective tissue and readily invade 3D collagenous matrices (Laskin 1992;Wolf et al 2003Wolf et al , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…It differs from most of the soft tissue tumors because of the fact that it is indeed slowly progressive, locally aggresive tumor and has a high rate of recurrence rates after surgical treatment. DFSP is a rare tumor, its exact incidence is not known [1][2][3][4][5]. Recently it has been reported that the overall incidence of DFSP in United States is 4.1 per million person-years [6].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the time initially painless lesion turn out to be a painful tumor. Moreover, ulceration along with discharge have been described for DFSP [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation